The impact of green climate fund portfolio structure on green finance: Empirical evidence from EU countries - Muhammad Mohsin; Azer Dilanchiev; Muhammad Umair (Ekonomika, 2023)
The financing sector drives the Future of Environmental Funds to achieve climate financing. In this study, we have employed panel regression analysis and the generalized two-step moment method (GMM) for the 25 EU countries from 2000 to 2021 to explore the relationship between green financing and the portfolio structure of green climate funds. According to the findings of this research, green financing significantly impacts quality economic growth. The GCFs enhance the capacity to channel public and private funding while contributing to de-risking more conventional forms of funding, increasing climate financing, and boosting the GCFs. In addition, the study concluded that Global Climate Support might fund nonbankable components of more significant "almost bankable projects" by analyzing the portfolio's policies and methods.
Keywords: 330; Financing Sector; Green Climate Funds (GCF); Green financing; EU countries